Microalgae (Chlorella vulgaris) attenuates aflatoxin-associated renal injury - Abdeen, Ahmed; Elsabagh, Rasha; Elbasuni, Sawsan S.; Said, Alshaimaa M.; Abdelkader, Afaf; El-Far, Ali H.; Ibrahim, Samah F.; Mihaela, Ostan; Fericean, Liana; Abdelfattah, Abdelfattah M.; El-Hewaity, Mohamed; Elbarbary, Nady; et al. (Frontiers in Pharmacology, 2023)
Aflatoxins (AFT) are ubiquitous environmental pollutants that are extremely dangerous for both human beings as well as animals. A safe, effective, and considerate strategy is therefore credited with controlling AFT intoxication. Therefore, our study aimed to evaluate the mitigating properties of Chlorella vulgaris (ChV) against AFT-induced nephrotoxicity and altered egg quality.Quails were randomized into Control group (receiving a normal diet); ChV group (1 g/kg diet);AFT group (receiving an AFT-containing diet); and the AFT-ChV group were given both treatments. AFT provoked kidney injury, exhibited by increased renal biochemical parameters and reduced protein levels. Malondialdehyde (MDA) levels dramatically increased as a consequence of AFT exposure, and glutathione (GSH) levels, superoxide dismutase (SOD), and glutathione peroxidase (GPx) activities were also decreased. Substantial up-modulation of the mRNA expression of the inflammatory cytokines (TNF-α, IL-1β, and IL-6) was additionally reported. Furthermore, AFT residues were detected in the egg compromising its quality and nutritional value. Contrarily, ChV supplemented diet suppressed the AFT-prompted oxidative stress and inflammation, together with enhancing the nutritional value and quality of eggs and decreasing AFT residues. These beneficial impacts are proposed to be attributed to its antioxidant and nutritional ingredients. The molecular docking dynamics confirmed the inflammatory and apoptotic protein targets for ChV. Our findings recommend that adding ChV supplements to foods might guard against nephrotoxicity brought on by AFT exposure.